Scaling ozone effects from seedlings to forest trees - Samuelson, Lisa (The New phytologist, 2001)
Biospheric ozone has become a widely distributed air pollutant, and a growing body of research indicates that ozone impacts forest health and productivity. Ozone effects are mediated by the ozone concentration present in the external environment and the movement of ozone into the leaf via the stoma. The cumulative dose received by the plant is, in the simplest terms, a function of ambient ozone concentration and stomatal conductance to water vapor. This relationship is important in understanding ozone flux into the leaf and subsequent ozone response in plants. Here, current progress in understanding ozone uptake in juvenile and mature trees is examined. Through an analysis of two long-term case studies, the significant uncertainty in assessing ozone effects on forests is pinpointed to be the scaling of ozone sensitivity from controlled seedling studies to large forest trees. A rigorous statistical and monitoring approach, which includes ozone uptake as a cause variable, may provide the missing information on processes that are known to be important to risk assessment of ozone impacts on forest trees. Contents Summary 21 I. Introduction 22 1. Background 22 2. Characterization of ozone exposure 22 3. The need for scaling 23 II. Scaling from seedling to tree, evidence from a Quercus rubra case study 24 1. Study background 24 2. Facilities and measurements 24 3. Ozone exposure dynamics 24 4. Above-ground processes 25 5. Below-ground processes 26 6. A process modelling exercise 27 7. Conclusions 28 III. Scaling from chamber to forest, evidence from a field case study 29 1. Study background 29 2. Field sites and measurements 30 3. Ozone exposure dynamics 30 4. Stomatal conductance and ozone uptake in forest trees 30 5. Conclusions 32 IV. Evidence from a scaling exercise 33 V. Concluding remarks 36 Acknowledgements 37 References 37